2020
DOI: 10.1101/2020.06.10.20126458
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Cardiology Services

Abstract: Objective: COVID-19 pandemic resulted in prioritisation of NHS resources to cope with the surge in infected patients. However, there have been no studies in the UK looking at the effect of COVID-19 work pattern on the provision of cardiology services. We aim to assess the impact of the pandemic on the cardiology services and clinical activity. Methods: We analysed key performance indicators in cardiology services in a single centre in the UK in the intervals prior and during the lockdown to assess for reducti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
18
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 4 publications
8
18
0
1
Order By: Relevance
“…The reduction in CVD contacts is consistent with reports from other UK studies. 18,41 Taken alongside findings of similar reductions in Emergency Department presentations and hospital admissions for cardiovascular outcomes in the UK, our findings highlight an area of major concern, 3,42 particularly as evidence from France indicates increased out-of-hospital cardiac arrest. 43 Severe COVID-19 affects the cardiovascular system; 44 hence, increased primary and secondary care presentations for CVD are expected.…”
Section: Discussionsupporting
confidence: 70%
“…The reduction in CVD contacts is consistent with reports from other UK studies. 18,41 Taken alongside findings of similar reductions in Emergency Department presentations and hospital admissions for cardiovascular outcomes in the UK, our findings highlight an area of major concern, 3,42 particularly as evidence from France indicates increased out-of-hospital cardiac arrest. 43 Severe COVID-19 affects the cardiovascular system; 44 hence, increased primary and secondary care presentations for CVD are expected.…”
Section: Discussionsupporting
confidence: 70%
“…Similar to Fersla et al in the United Kingdom, we found a significant drop in cardiology units' admissions and a significant reduction in the overall cardiology activities including outpatient clinics, investigations, procedures and community services such as cardiac rehabilitation (6).…”
Section: Discussionsupporting
confidence: 89%
“…It is worth mentioning that because this pandemic is unprecedented and its impact on the delivery of cardiology services have not been much explored, data on the relationship between COVID-19 and cardiology services are scarce. Similar to Fersla et al in the United Kingdom, we found a signi cant drop in cardiology units' admissions and a signi cant reduction in the overall cardiology activities including outpatient clinics, investigations, procedures and community services such as cardiac rehabilitation (6). The new adaptation of the consultation programs was not appreciated by half of the clinicians, probably because it decreased their workload and consequently resulted in a reduction of their remuneration.…”
Section: Discussionsupporting
confidence: 83%
“…This implies the cautious generalization of the study ndings. However, the results of this pilot study were similar to trends seen abroad (6). Hence, the ndings imply a scale-up in the delivery of cardiology services in Africa during and after the pandemic geared at better patient management COVID-19 patients.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation